Analisis Yuridis terhadap Penangkapan dan Penahanan Demonstran dalam Perspektif Pelanggaran Hak Asasi Manusia - Varik Farsyak; Ariel Lian Pratama; Aldo Kurniawan (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study examines the legal issues surrounding the arrest and detention of demonstrators, which have the potential to violate human rights in Indonesia. Using normative legal research methods with historical, case-based, and analytical approaches, this study analyzes the gap between progressive legal norms and repressive practices in the field. The results show that the arrest and detention of demonstrators often violate human rights due to several factors: first, the gap in implementation between the provisions of the Criminal Procedure Code (KUHAP) and international human rights standards and field practice; second, the weak understanding of human rights principles by officials and the lack of adequate training; and third, the practice of mass arrests without clear procedures, which contradicts the principle of individual criminal responsibility. This study identifies three legal mechanisms to provide protection: preventive measures through internal and external oversight; repressive measures through pretrial and criminal legal remedies; and restorative measures through mediation and institutional reform. The effectiveness of these mechanisms is hampered by institutional independence, procedural accessibility, institutional capacity, and public legal awareness. This study recommends comprehensive reform of the human rights protection system, strengthening oversight, and shifting the paradigm of handling demonstrations from a repressive approach to a human rights-based approach.